PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE MATERI MENGENAL HAK DAN KEWAJIBAN PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS I SD NEGERI 20 SITIUNG - Umaiyah; M. Anggrayni; Wiwik Okta Susilawati (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research is motivated by the difficulties faced by educators in developing learning media that meet the needs of students. As a result, educators tend to use simple media or those readily available in the school environment. The purpose of this study is to develop a puzzle-based learning medium for the topic Recognizing Rights and Responsibilities in the Pancasila Education subject for Grade I students at SD Negeri 20 Sitiung. This study is a type of Research and Development (R&D) using the 4-D development model (Define, Design, Develop, Disseminate). The validation results show that the developed learning media have a high level of validity: graphical aspects scored 90% (very valid), content 89.2% (very valid), language 86.6% (very valid), questions 89.2% (valid), and teaching module 88% (very valid). The practicality level of the puzzle-based learning media as assessed by teachers reached 91% (very practical), while assessments from students reached 93.42% (very practical). The effectiveness of the media, based on the students’ learning outcomes test, reached an average of 91.30%. Therefore, it can be concluded that the development of the puzzle-based learning media for the topic Recognizing Rights and Responsibilities in the Pancasila Education subject for Grade I at SD Negeri 20 Sitiung is valid, practical, and effective for use in the learning process. Keywords: Puzzle Media, 4-D Model, Pancasila Education, Elementary School